Exploring postgraduate students’ challenges in doing master research - Saidin, Khaliza (2016)
Research activity involves investigation which gives impact to intelectuality, creativity and discipline among postgraduate students. The purpose of this study is to explore postgraduate students’ challenges while completing their Master Research in one of the public universities in Malaysia. The subjects of this study were 25 postgraduate students undergoing their dissertation which is a requirement to graduate. This study used open ended interview approach to explore the challenges on doing master research. For the analysis of the data, thematic approach was used to get information from the students. The study found that there are four main challenges that the postgraduate students face in doing dissertation which are different field, time management, lack of research knowledge and supervision. Most of the students reported that the field of research that they are doing is different from their previous knowledge. Students also found that it was difficult for them to balance their time between their job and studies. Another challenge is they have never explored the research when they are doing their degree. Students also said that they have to wait for a long time for the appointment of their supervisor. These four challenges are contributing factors for postgraduate students in completing their dissertation and therefore universities need to come up with a more effective strategy to help these students overcome the challenges in order to produce intellectual and skilled researchers.